The Relationship Between the Decrease in Longitudinal Systolic Function and High Filling Pressures in The Hypertensive Patients - Taleb Bendiab, Nabila Soufi; Benkhedda, Salim; Henaou, Latifa (Clinical Medicine And Health Research Journal, 2023)
Introduction: Heart failure with preserved LVEF (left ventricular ejection fraction) is an important cause of mortality and morbidity in hypertensive patients. A close correlation between the achievement of diastolic function and longitudinal systolic dysfunction could have several explanations, first the diastole is a dependent energy process, especially during its first phase, it also includes active systolic components during the iso volumetric relaxation phase. The objective of this work is to determine the effect of diastolic function on the drop in GLS (global longitudinal strain) in hypertensive patients with preserved LVEF. Materials and methods: This work is to perform in a series of 400 hypertensive patients (aged 25-75 years) an echo study full cardiographic, including the study of the systole-diastolic function, and the evaluation of the function by the longitudinal 2D strain. Results: Of the 400 hypertensive patients, 356 patients (89%) had impaired diastolic function, of which 46 patients (13%) had high filling pressures.144 patients had a high LA(left atrial) volume, of which 46 patients had high filling pressures. Of the 144 patients with high LA volume 118 patients (81.9%) had low GLS. The mean of blood pressure was significantly higher in patients with low GLS. There is a statistically very significant relationship between lower GLS, increased left atrium volume, and increased left ventricular filling pressures in hypertensive patients. Conclusion: The decline in longitudinal index of function, despite preserved LVEF, correlates well with increased left atrial volume, filling pressures in hypertensive patients with LVH (left ventricular hypertrophy). The association between hypertension with LVH and the deterioration of asymptomatic diastolic function is well recognized.